Pengaruh Ukuran Umbi terhadap Pertumbuhan Awal Tiga Varietas Bawang Merah (Allium ascalonicum L.) - Susilawati, Susilawati; Sodikin, Erizal; Sulaiman, Firdaus; Irmawati, Irmawati (Seminar Nasional Lahan Suboptimal, 2023)
Susilawati, S., Sodikin, E., Sulaiman ,F., & Irmawati, I. (2023). The effect of bulb size on the initial growth of three varieties of shallot (Allium ascalonicum L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 151-162).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Both vegetative (using bulbs as planting material) and generative (using seeds) methods can be used to cultivate shallot plants. Although using bulbs is simpler, it has a number of drawbacks, including the need for more seeds, relatively high costs, and the challenge of planning a planting timetable. In order to support the growth of three types of shallots, this study sought to assess the strength of the correlation and regression models of the bulb features.  The study was carried out during June and July 2023 in Tanjung Pering Village, Indralaya Utara Subdistrict, Ogan Ilir, South Sumatra, at coordinates 003 13'00" LS and 104 38'16" E. A Randomized Block Design with two components and three replications was employed in the study. The first factor is the utilization of three different varieties: Bauji, Bima Brebes, and Tajuk. The second component is bulb size, which comes in three sizes: small (1.5 cm), medium (1.5 cm to 2.0 cm), and large (>2.0 cm). The research plot measured 150  cm by 100 cm, and each treatment plot had 21 plants. The parameters that were measured included the bulb character, which included the diameter, weight, length, and volume of the bulb, and the bulbs initial growth, which included the leaf length, number of leaves, tillers, and SPAD value. Based on the coefficient of determination (R2), the findings demonstrated that the linear zero-intercept model consistently performed better than other regression models in correlating bulb diameter with bulb length, weight, and volume. The Tajuk variety had the most leaves and tillers but the lowest SPAD score when varieties and bulb sizes were combined early in growth. Shallot plants develop best in their early stages on little bulbs. Conclusion the most accurate model for correlation between bulbs characters uses a zero intercept linear regression model.